Death-stricken survivor mother: the lived experience of near miss mothers - Sedigheh Abdollahpour; Abbas Heydari; Hosein Ebrahimipour; Farhad Faridhoseini; Talat Khadivzadeh (BMC, 2022)
Plain language summary A maternal near miss (MNM) is a life-threatening condition experienced by a mother with organ failure due to severe maternal morbidity. Near miss mother (NMM) experiences adverse outcome such as physical, emotional, and psychological consequences after near miss event. Understanding the meaning of these mothers' lived experience and listening to their voices will help in reducing the burden of complications and will be effective in rehabilitating the disability created in their life. "Death-stricken survivor mother" was the central emerged theme resulting from the study of phenomenology. The main body of this theme reflects the severe physical, psychological burden and vicissitudes life. Server maternal morbidity due pregnancy and childbirth, have made NMM mother's life very different from those of normal mothers. The living conditions of these mothers are mixed in all aspects of the MNM event. Long-term physical and psychological damages they have endured, should be on the agenda of women's health policy makers to support them for years after discharge with integrated care.